HISTORY OF EARLY CHEMICAL ENTERPRISE IN UZBEKISTAN - Холикулова Ш. Б. (TARIXIY TADQIQOTLAR, 2025)
In this article, the author examined the history of the construction of the first chemical plant in the Republic of Uzbekistan, Shorsuv Oltingugut, and also described its goals and objectives. In the process of preparing the article, some documents stored in the funds of the National Archive were presented to the attention of scientists for the first time. The author summarized his thoughts on the basis of these documents.